Pigeon as a model to study peripheral projections from the horizontal semicircular canal vestibular apparatus to a brainstem target immunoreactive for AMPA - Rocha,João Roberto (2021)
ABSTRACT Purpose: To evaluate whether the pigeon (Columba livia) is a good model for evaluating the vestibular system involved with postural maintenance during movement. Methods: This study maps the brainstem targets of the horizontal ampullary inputs from the vestibular periphery of the pigeon. We used biotin dextran amine (BDA) injection in horizontal semicircular canal (HSCC), immunohistochemistry for GluR2/3 and GluR4 AMPA and computerized histomorphology reconstruction. Results: Our results show the same distribution pattern with ipsilateral projections to vestibular nuclear complex (VNC) from the HSCC, with the majority of labeled fibers being, long, thin, with few varicosities and many ramifications. Horizontal semicircular canal projections achieve neurons belonging to all nuclei of the VNC with exception of dorsal portion of lateral vestibular nucleus and this area express GluR2/3 and GluR4 AMPA receptors reinforcing the idea of glutamate participation in these connections. Conclusions: Pigeon is an appropriated experimental model to study of projections of HSCC and reinforcing the information that the vestibular system has strong relation with the fast responses necessary for postural control. Moreover, its phylogenetic organization apparently conservation, also seems to be a fundamental characteristic for vertebrates.